EDUCATION OF YOUTH IN THE SPIRIT OF PATRIOTISM DEVELOPMENT OF THE CULTURE OF LEGAL CONSCIOUSNESS - Kudaybergenova Tajikhal Kuchkarovna (Galaxy International Interdisciplinary Research Journal, 2021)
This article is devoted to teaching youth legal education and the formation of a culture of legal education.